2009
DOI: 10.1021/bi900475k
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Priming Dynamics: Mechanisms of Integrin Antagonist-Promoted αIIbβ3:PAC-1 Molecular Recognition

Abstract: This investigation addressed the paradox that disintegrins and small RGD-ligands readily bind to the resting alphaIIbbeta3 integrin, while macromolecules with similar integrin recognition motifs require an activated, or primed, receptor. Three structurally similar pharmaceutical integrin antagonists (eptifibatide, tirofiban, and roxifiban) were each incubated with resting alphaIIbbeta3; after drug wash-out, the receptor's ability to recognize PAC-1, an activation-dependent IgM with an RYD integrin-targeting si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 52 publications
1
61
0
1
Order By: Relevance
“…Activation of CASP3 may also sensitize cancer cells to other agents, such as chemotherapy. In this study, we sought to analyze whether a caspase 3 activator, PAC-1, 25 which activates procaspase-3 by chelating zinc and thus relieves the zinc-mediated inhibition of this zymogen, had anti-proliferative effects in lung adenocarcinoma cells, and whether there were synergistic effects in combination with Cis, a key chemotherapeutic agent, in these cancer cells. Our IHC data regarding CASP3 expression showed that CASP3 was overexpressed in some lung cancers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of CASP3 may also sensitize cancer cells to other agents, such as chemotherapy. In this study, we sought to analyze whether a caspase 3 activator, PAC-1, 25 which activates procaspase-3 by chelating zinc and thus relieves the zinc-mediated inhibition of this zymogen, had anti-proliferative effects in lung adenocarcinoma cells, and whether there were synergistic effects in combination with Cis, a key chemotherapeutic agent, in these cancer cells. Our IHC data regarding CASP3 expression showed that CASP3 was overexpressed in some lung cancers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A Biacore T100 SPR platform ( 22,23 ) was used to quantify the interaction of LDL with immobilized BGN. In the fi rst step, the dextran surfaces of a CM5 biosensor chip (Biacore, Inc.; Piscataway, NJ), for both reference and sample channels, were activated for amine coupling ( 22 ).…”
Section: Ldl-bgn Interactionmentioning
confidence: 99%
“…In the fi rst step, the dextran surfaces of a CM5 biosensor chip (Biacore, Inc.; Piscataway, NJ), for both reference and sample channels, were activated for amine coupling ( 22 ). Following surface activation, an antigen affi nity-purifi ed polyclonal goat IgG, specifi c to BGN core protein (R and D Systems; AF2667), was covalently coupled to the dextran surface of the chip through its lysine residues, reproducibly yielding a sparse IgG monolayer in both channels signifi cant positive association between the percentage of plasma CE as CO and carotid artery intima-media thickness in patients with preclinical atherosclerosis ( 13 ).…”
Section: Ldl-bgn Interactionmentioning
confidence: 99%
“…studies show fibrinogen binding is a time-dependent multistep process leading to higher-affinity and lack of reversibility. 9,10,[12][13][14][15][16][17][18][19][20][21][22] (2) When reversibly dissociated, both aIIb and b3 can bind to immobilized fibrinogen. 16 (3) Platelets can adhere to fibrinogen fragments lacking g-404-411, 23,24 but it is unclear whether the platelets need to be activated in order to bind.…”
Section: Introductionmentioning
confidence: 99%